Political risk management on international construction projects - Muchenga, Isaac (Department of Construction Economics and Management, 2016)
This research examines the micro -political risks affecting international construction projects in Namibia and whether these risks are effectively managed. A case study research design was used for the study and the findings were that key threat risks identified in this context were repudiation, contract problems, labour unrest, hostile press, delay in permit approvals while local ownership requirements and expatriate labour restrictions are both threat and opportunity risks . It further emerged that qualitative (heuristic) techniques were commonly used in an ad hoc fashion for risk assessment and that the risk management strategy of cooperation was the most preferred. In addition, evidence suggest s that the execution phase is most prone to micro political risk. A significant number of the micro -political risks identified arise from the host government, while the balance arise from the host society. These findings are likely to apply to other international construction projects in Namibia and have serious implication s for the role of government in the success or failure of infrastructural projects which are badly needed for national development. Therefore, the Namibian Government can positively contribute through introduction of regulations, laws or amendments to laws that enhance opportunities, minimise downside risk, and thereby reduce overall construction costs on international construction projects in the country. It is recommended that systematic risk management in which both qualitative and quantitative techniques are used for risk assessment, be adopted in dealing with micro political risks associated with international construction projects in Namibia. Additionally, tertiary institutions offering risk management training need to focus on qualitative methods to facilitate maximum benefit when these methods are applied by their graduates. The existence of both threat s and opportunities in the micro -political risk environment in international construction means contractors in international construction need to be on the lookout for downside risks as well as opportunities.